Excellent reusable chitosan/cellulose aerogel as an oil and organic solvent absorbent. (1st July 2018) - Li, Zhanying; Shao, Lin; Hu, Wenbin; Zheng, Tingting; Lu, Lingbin; Cao, Yang; Chen, Yongjun
Highlights: Chitosan successfully reacted with oxidized cellulose hydrogel. The aerogel exhibited a high oil/water selectivity after modification. The aerogel exhibited high absorption capacity for oils and organic solvents. Reinforce of structure made the aerogel possess high recyclability. Abstract: Absorption is one of the most important methods for oil spill cleanup. An ideal absorbent is expected to possess advantages of low cost, green, high absorption capacity and excellent reusability. In this paper, a new kind of cellulose aerogel was successfully fabricated via cellulose oxidation, crosslinking, freeze drying and cold plasma modification. The obtained aerogel (water contact angle up to 152.8°) exhibited outstanding oil/water selectivity and high absorption capacity (13.77–28.20 g/g) for various oils and organic solvents. What's more, this kind of aerogel could be reused by simple compression. The absorption-desorption process could be repeated for at least 50 cycles. Through the kinetic analysis, it was found that the pseudo-second order model was more appropriate for the aerogel's oil absorption process. Owing to its low cost, hydrophobicity, high absorption capacity and excellent reusability, this kind of aerogel is expected to be used in oils and organic solvents spill cleanup and oil/water separation field.